Examining the Connection between Quality Education and Employability: Insights from Educators and Individuals (Solukhumbu Multiple Campus Research Journal, 2025)
The widespread notion, among both the public and scholars, is that developing countries like Nepal experience disparities in educational quality. Issues are regularly flagged in this regard at the policy level, academia, media, and public forums. Nevertheless, there is no research-based discourse about what “quality” means and how it is designed and implemented in different domains. In the case of Nepal, which this article focuses on, it is often presumed that education in public schools is outmoded, impractical, limited in hands-on training, and lower in standards compared to that in private schools. Therefore, the core objective of this study is to examine the nexus between quality education and occupational skills, drawing insights from educators and individuals. This article reviews a literature review and analysis of data, including surveys, interviews, and focus groups, to develop a framework for describing and discussing quality education in the context of Kathmandu, Nepal. Anchored in the interpretivist paradigm, this study employs an interpretative phenomenological methodology to explore and elucidate the lived experiences of the participants. The findings depict that good teaching, a supportive learning environment, and active involvement in extracurricular activities play a significant role in providing quality education, which helps students become professionally competent.